2001
DOI: 10.14411/fp.2001.006
|View full text |Cite
|
Sign up to set email alerts
|

Gill parasites of Cephalopholis argus (Teleostei: Serranidae) from Moorea (French Polynesia): site selection and coexistence

Abstract: Abstract. The distribution and coexistence of gill ectoparasites of 121 specimens of Cephalopholis argus Bloch et Schneider, caught between October 1994 and October 1995, were investigated. Adults of the monogenean Benedenia sp. and copepod Hatschekia sp., the larval caligid copepod Caligus sp. (copepodite and chalimus stages), and praniza larvae of the isopod Gnathia sp. were found. All species were aggregated within the host population. Infracommunities were poor, with only 40.5% of fish infected by two para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…These differences in site specificity may be due to different feeding and egg-release strategies, developed during phylogenetic evolution (Lester 1980, Mladineo et al 2010). Caligus bonito also shows site specificity on the gills of the skipjack tuna; according to Lo & Morand (2001), the significant differences in locations between adults and chalimi of C. bonito reflect different ecological requirements.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in site specificity may be due to different feeding and egg-release strategies, developed during phylogenetic evolution (Lester 1980, Mladineo et al 2010). Caligus bonito also shows site specificity on the gills of the skipjack tuna; according to Lo & Morand (2001), the significant differences in locations between adults and chalimi of C. bonito reflect different ecological requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Gnathiid isopod larvae have been studied extensively in coral-reef fish (Lo et al 1998;Lo and Morand 2001;Rohde 2005) and a variety of others. González et al (2004) reported that gnathiid infestation in common dentex (Dentex dentex) from the western Mediterranean Sea (Balearic Islands) ranged from 1 to 201 per fish.…”
Section: Discussionmentioning
confidence: 99%
“…Gnathiid larvae are one of the most common ectoparasites of elasmobranchs and teleosts (Nagel and Grutter 2007;McKiernan et al 2005;González and Moreno 2005;Rohde 2005;Smit et al 2003;Tinsley and Reilly 2002;Lo and Morand 2001;Upton 1984), including the Serranidae (Genc et al 2005). Gnathiids have low host specificity as well as highly dynamic movements onto and off the host fish (Grutter 1994;Chambers and Sikkel 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, although the spatial distribution of copepods has been well documented (e.g., Hanek and Fernando 1978;Benz and Dupre 1987), the coexistence of copepod species has been studied much less (Bashirullah 2000). Further, investigations considering the co-occurrence of monogeneans and copepods are uncommon, and the majority of them have addressed motile copepods (Ramasamy et al 1985;Geets et al 1997;Nie 2000;Lo and Morand 2001;Yao 2003). Additionally, some reports have focused solely on the abiotic factors allowing parasite maintenance on hosts (Barker and Cone 2000) or on the pathological consequences of such co-infections for their hosts (Ojha and Hughes 2001).…”
Section: Introductionmentioning
confidence: 99%